Do IFC Investments Reduce Poverty by Creating Jobs? : A Case Study of a Manufacturing Investment in Indonesia - Datar, Gayatri; Diamond, Alexis (International Finance Corporation, Washington, D.C., 2017)
This impact evaluation uses econometric techniques to assess the social and economic impact of an IFC investment in Ecogreen Oleochemicals in Indonesia. This investment doubled the capacity of an Ecogreen plant in the Kabil district on the island of Batam. The authors use the synthetic control methodology and household level survey data from 1994-2009 to assess whether measureable impacts are observed after the investment. The authors find that monthly expenditures per capita in the Kabil district grew by 165,000 more rupiah (210 US dollars per year) than in the control district, representing a 22 percent increase over the 2009 level of expenditures of 785,000 rupiah (1,000 US dollars per year) in the control district. When this 210 US dollars is extrapolated to the 19,000 people that live in the treated district, the total annual impact in 2009 is 4 million US dollars. Aggregating each year since 2005, the impact over 4 years was $6.8 million. However, there has been no significant increase in Kabil in employment, and in fact a decrease in formality. Based on qualitative interviews in Batam, this expected. The investment resulted in the employment of many high-paid workers, as Ecogreen hired mostly skilled labor with college degrees in the natural sciences. These workers generally migrated from outside of Batam to join Ecogreen, thus boosting the local economy through additional demand for products and services from local enterprises. As expenditures per capita is a measure of the welfare of the local economy, this increase is expected. However, employment did not increase faster than the control group, possibly demonstrating that existing local businesses grew, and this growth was not spread to additional businesses and additional employment. Additionally, employment rates in Batam have historically been high (90-95 percent) given that it is a Special Economic Zone, so increases are not likely to be large and therefore difficult to observe in the data. Finally, formality actually decreased, likely because much of the job growth in the local economy was in the informal sector. This evaluation demonstrates that investments in skilled labor can have positive spillover effects to the local economy. It also represents the first time the IFC has used econometric methods and survey data to understand induced impact. This evaluation therefore also provides a methodological example for how the IFC can evaluate its impact in the future.